Peranan Ekonomi Moneter Syariah dalam Upaya Mengatasi Kemiskinan di Indonesia - Bunga Ahista Rania; Marcelino Rizki Suryanto; Athfiatul Ashfiyah; Rasidah Novitasari (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The focus of sharia monetary economics is to apply Islamic rules in financial management to improve welfare and reduce poverty. The system emphasizes the concepts of justice and equity and avoids elements such as usury, uncertainty, and excessive speculation. The sharia monetary economy aims to increase income equality by using instruments such as zakat, infaq, alms, and waqf. This study shows how sharia monetary economics can help overcome poverty in Indonesia, especially through sharia financial instruments such as microfinance institutions and yield principles. Studies show that Islamic finance improves economic stability and helps people achieve sustainable prosperity.